Combination of Thermal-Treated Kelulut (Stingless Bee) Honey and Phyllanthus niruri Extract: Evaluation on Antibacterial Activity Against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Staphylococcus epidermidis - Razali, Muhammad Faiz; Aripin, Jenorico; Iderus, Nadia Natasha; Mohd Adnan, Nuraisha Syazwani; Mohd Fauzi, Noor Akhmazillah (Trends in Sciences, 2023)
Kelulut honey (KH) has a broad spectrum of antibacterial effects that conceivably deteriorate upon heat treatment. However, further synergistic combinations with plant extract might be of value in improving the bactericidal capacity. Therefore, this study reports on the combination of KH with Phyllanthus niruri extract as both are independently known to be bactericidal. P.niruri extract was incorporated into 2 types of KH; untreated and thermal-treated (50, 60 and 70 °C for 5, 10, 15 and 30 min); and tested against 4 bacterial strains (Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Staphylococcus epidermidis) through disc diffusion method. Untreated KH in general had a bigger inhibition zone than thermal-treated. The inhibition reaction was considered sensitive (> 8 mm) against S.aureus, E.coli and P.aeruginosa. Whereas, the effect of thermal treatment on KH was significantly (p < 0.05) apparent against S.aureus, in which the inhibition zones were mostly not sensitive (< 8 mm). In combination, the mixture of 70:30 (KH:P.niruri) had the highest inhibition zone as compared to other ratios. However, the interaction was only deemed to be synergistic with untreated KH, principally against S.aures and P.aeruginosa. The results thus showed the vast inhibition spectrum of KH as affected by thermal treatment and combination with P.niruri extract. Thermal treatment reduced the bactericidal of KH while incorporation with P.niruri extract could synergistically improve the bactericidal with a ratio of 70:30. HIGHLIGHTS Untreated Kelulut honey (KH) demonstrated antibacterial activity against bacterial strains tested Thermal treatment reduced the antibacterial activity of KH Combination with niruri extract showed an increment in antibacterial activity A Synergistic combination was attained with the ratio of 70:30 (v/v) of KH:niruri extract GRAPHICAL ABSTRACT